Influence of Diabetes Mellitus on the Incident of Stroke: Meta-Analysis - Mubarok, Ahmad Syauqi; Kurniawan, Hendra Dwi; Verasita, Prissy; Azmiardi, Akhmad; Puspitasary, Kiky (GLOBAL HEALTH SCIENCE GROUP, 2023)
Blood vessel disorders can occur due to the narrowing and hardening of the artery walls, which is called atherosclerotic plaque. Stroke is a serious health problem because of the high mortality and morbidity rates and its impact can cause chronic disability and occurs not only in elderly people but also in young people. This study aims to estimate and analyze the effect of diabetes mellitus on the incidence of stroke. This research is a systematic review and meta-analysis research using the PRISMA diagram. Article searches were carried out based on the PICO Model eligibility criteria. P= DM patient; I= Diabetes mellitus; C= Normal blood sugar; O= Stroke. The articles used come from Google Scholar. With keywords including